Factors Influencing Entrepreneurial Intentions Among Chilean Secondary Vocational Students; [Factores Que Influyen en Las Intenciones Emprendedoras de Los Estudiantes Secundarios Chilenos de Formación Técnico-Profesional] - Torres-Ortega, J; Hernandez-Munoz, V (Emerald Publishing, 2024)
Purpose: This paper aims to determine the effect of a set of factors (attitude toward entrepreneurship, perceived behavioral control or entrepreneurial self-efficacy, previous experience, internal locus of control and entrepreneurial alertness) on the entrepreneurial intentions of Chilean secondary vocational school students. Design/methodology/approach: An online survey was sent to all secondary-level students from four Chilean vocational schools (3,052 students). A total of 1,644 valid questionnaires were received. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). Findings: The results show that attitude toward entrepreneurship and perceived behavioral control positively and significantly impact the students’ entrepreneurial intentions, but not the previous experience. Research limitations/implications: Since this research was carried out in a specific reality, the results may lack generalizability. Also, the proposed model requires further development through the incorporation of other factors. It is then suggested to replicate this study in other countries as well as to incorporate new variables and test new relationships. Practical implications: Entrepreneurship education programs at the secondary level should emphasize changing/stimulating adolescents’ attitudes toward entrepreneurship as well as improving their confidence in their entrepreneurial abilities. Originality/value: This is one of the few studies that provide empirical evidence about the determinants of entrepreneurial intentions in adolescents, particularly in Latin America, and with a large sample. © 2024, Emerald Publishing Limited.